The effect on the patient flow in a local health care after implementing reverse triage in a primary care emergency department: a longitudinal follow-up study - Timo Kauppila; Katri Seppänen; Juho Mattila; Johanna Kaartinen (Taylor & Francis Group, 2017)
Objective: Reverse triage means that patients who are not considered to be in need of medical services are not placed on the doctor's list in an emergency department (ED) but are sent, after face-to-face evaluation by a triage nurse, to a more appropriate health care unit. It is not known how an abrupt application of such reverse triage in a combined primary care ED alters the demand for doctors' services in collaborative parts of the health care system. Design: An observational study. Setting: Register-based retrospective quasi-experimental longitudinal follow-up study based on a before-after setting in a Finnish city. Subjects: Patients who consulted different doctors in a local health care unit. Main outcome measures: Numbers of monthly visits to different doctor groups in public and private primary care, and numbers of monthly referrals to secondary care ED from different sources of primary care were recorded before and after abrupt implementation of the reverse triage. Results: The beginning of reverse triage decreased the number of patient visits to a primary ED doctor without increasing mortality. Simultaneously, there was an increase in doctor visits in the adjacent secondary care ED and local private sector. The number of patients who came to secondary care ED without a referral or with a referral from the private sector increased. Conclusions: The data suggested that the reverse triage causes redistribution of the use of doctors' services rather than a true decrease in the use of these services.